Fiscal space for child-sensitive social protection in the MENA region - Carolina Bloch; Charlotte Bilo; Imane Helmy; Rafael Guerreiro Osorio; Fábio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
Social protection policies can help address the multifaceted nature of child poverty and improve children's well-being, especially in the areas of education, health and nutrition. Providing adequate social protection to children is particularly relevant in the Middle East and North Africa (MENA), as multidimensional child poverty remains a major concern in the region. Moreover, a large share of the population of MENA will soon transition into their most productive age, clearing the way for a demographic dividend. This demographic transition presents a unique opportunity for economic growth in the region, due to its larger-than-usual share of working-age adults.
Keywords: 330; fiscal space; child-sensitive; social protection; MENA